The technology for reconditioning an LBC Cylindrical Support Spindle - Gabriel Gârleanu; Delia Gârleanu; Marinela Marinescu; Larisa Butu (Journal of Research and Innovation for Sustainable Society)
The article presents the reconditioning technology for the bearing housing of a cylindrical support spindle used in sheet rolling. Due to the pressing forces required for rolling, the bearings are subjected to extremely high stress. In this particular case, one of the bearings seized, causing the shaft to rotate continuously. As a result, the end of the shaft (the spindle) wore down across the entire width of the bearing. The wear level reached nearly 5 mm in radius, which is a significantly high value. The article outlines the technological steps for repair, the types of filler materials that can be used, as well as the welding and inspection technology